Holt physical science - Ramsey,William L.; Holt, Rinehart, and Winston, inc. (New york Holt,Rinehart and Winston, 1982)
Design to help students better understand important chemistry and physics concepts. Animated modules guide students step-by-step through math problems frequently encountered in chemistry and physics.
Title from disc label.
Production level cataloging.
System requirements for Macintosh: 7200/90MHz processor; 16MB RAM (with 24MB RAM for concurrent Internet connection); System 7.5 to 8.0; 20MB free hard drive; color monitor with 8-bit (256 color), 640 x 480 x 256 display capacity, 16-bit (thousands of colors); compatible printer; 4x CD-ROM drive.
System requirements for Windows: Pentium PC; 16MB RAM (with 24MB for concurrent Internet connection); 4X CD-ROM drive; color monitor with 8-bit (256 color) 640 x 480 display capacity; 15MB free hard drive; sound blaster compatible audio; compatible printer.
Keywords: Physics -- Study and teaching; Science -- Study and teaching